COMPARATIVE ANALYSIS OF THE WATER QUALITY AT MUREȘ RIVER BASIN BASED ON MEASURED PARAMETERS AND WATER POLLUTION INDEX - ELENA-VIOLETA BLIDAR; SIMONA GAVRILAȘ; CLAUDIU-ȘTEFAN URSACHI; SIMONA PERȚA-CRIȘAN; FLORENTINA-DANIELA MUNTEANU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The present study focuses on monitoring water quality in the Mureș River basin, analyzing three sections (Săvârșin, Arad, Nădlac) from 2017 to 2020. Key parameters such as pH, electrical conductivity, dissolved oxygen (DO), chemical and biochemical oxygen demand total nitrogen, phosphates, chromium, copper, zinc, arsenic, and phenol were evaluated using statistical analysis and a global pollution index. The findings confirm the null hypothesis, showing that parameter variations across sections are random and have no significant influence from specific industrial or agricultural activities. Statistical results align with the global pollution index, validating the analysis